Islamization of the Invinsible Hand Concept by Adam Smith: A Reconstruction towards Islamic Key Principles - Muhammad Faqih Nidzom; Muhammad, Allan; Kamil, Rizvan Falah (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2025)
This study aims to Islamize Adam Smith’s concept of the invisible hand, which has long been regarded as a central pillar of capitalist economic theory. The invisible hand describes a free market mechanism in which individuals pursuing self-interest unintentionally contribute to collective welfare. While this theory emphasizes efficiency, it has been criticized for neglecting morality, justice, and equity. From an Islamic economic perspective, these dimensions are essential, as economic activity must be aligned with values of tawḥīd (monotheism), justice, and social responsibility. The research employs a qualitative approach through literature review and conceptual analysis. The literature review examines Adam Smith’s The Wealth of Nations and The Theory of Moral Sentiments, alongside classical and contemporary Islamic economic writings. Conceptual analysis is then used to assess the compatibility between the invisible hand and Islamic principles, particularly the role of zakat, ḥisbah, and maqāṣid al-Syarīʿah in shaping economic justice and social welfare. The results show that Smith’s invisible hand can be reconstructed by integrating Islamic values, thereby producing a more equitable economic model. While self-interest remains a driving force for efficiency, Islamic principles such as distributive justice through zakat, ethical oversight through ḥisbah, and alignment with maqāṣid al-Syarīʿah ensure that markets also serve moral and social objectives. The implication of this study is twofold: theoretically, it contributes to the enrichment of Islamic economic thought; practically, it offers policymakers an alternative framework for designing economic systems that are not only efficient but also just and welfare-oriented.